HUBUNGAN CACING TANAH DENGAN KONDISI FISIK, KIMIA DAN MIKROBIOLOGIS TANAH MASAM ULTISOL DI DAERAH LAMPUNG UTARA - Wibowo S (AgriPeat, 2015)
A study has been done to know relation of earthworm with physic, chemist and microbiologic condition of ultisol acid soil in North Lampung, Sumatera. The research indicated there was strong positive correlation between contents of light and moderate fractions of soil organic matter and Corganik with earthworm population. There was strong positive correlation between contents of total fraction, light and moderate fractions of soil organic matter, C-organic and earthworm population with their freshweight. There was strong positive correlation between contents of total fraction, moderate and heavy fractions of soil organic matter, N-total and earthworm freshweight with sum of their cocoons. There was strong positive correlation between contents of light and moderate fractions of soil organic matter, C-organic, N-total and earthworm freshweight with weigth of their casts. The population, freshweight, sum of cocoons and casts weight of eartworms have positive correlation with soil porosity. Soil temperature have negative correlation on all of variables. Sum of fungi and totalmicroorganisms have not strong correlation on the earthworms. The low of soil pH have not negative effect on the earthworms, it was suspected because which was lived in there were all of adaptable species with ultisol acid soil.